Glyco-Engineering Methods and Protocols - Castilho, Alexandra.; Castilho, Alexandra. (Methods in Molecular Biology, 2015)
Conceived with the intention of providing an array of strategies and technologies currently in use for glyco-engineering distinct living organisms, this book contains a wide range of methods being developed to control the composition of carbohydrates and the properties of proteins through manipulations on the production host rather than in the protein itself. The first five sections deal with host-specific glyco-engineering and contain chapters that provide protocols for modifications of the glycosylation pathway in bacteria, yeast, insect, plants, and mammalian cells, while the last two sections explore alternative approaches to host glyco-engineering and selected protocols for the analysis of the N-glycans and glyco-profiling by mass spectrometry. Written for the highly successful Methods in Molecular Biology series, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and tips on troubleshooting and avoiding known pitfalls. Authoritative and extensive, Glyco-Engineering: Methods and Protocols offers vast options to help researchers to choose the expression system and approach that best suits their intended protein research or applications.